2013
DOI: 10.1177/2158244013476052
|View full text |Cite
|
Sign up to set email alerts
|

The Internet Marketing of Disney Theme Parks

Abstract: The purpose of this study was to analyze the portrayal of gender and race in the images on the official Disney websites used to market five theme parks: the Disneyland Parks in California, Paris, Tokyo, and Hong Kong, and the Magic Kingdom in Florida. This is important because of the growth of e-commerce, Disney’s global influence, and the potential impact on those who view the images. The 452 images that had Disney human characters, human-like characters, animals, cast members, or guests were coded for gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Returning to the questionnaire, when asks about people's favourite character in Disney, the answers vary a lot. But after the analysis of those answers, there are 6 people who don't have any favourite character; 16 people's favourite characters' genders match with their own genders, according to the calculation, it is about 61.54%; the other 4 people's genders don't match with the genders of their favourite characters [8]. However, the percentage of those results are adequate for us to conclude that Disney does consider people's gender identity while designing the characters, and characters may be more attractive to people of the same gender [9].…”
Section: Brand Personalized Customization According To Identitiesmentioning
confidence: 99%
“…Returning to the questionnaire, when asks about people's favourite character in Disney, the answers vary a lot. But after the analysis of those answers, there are 6 people who don't have any favourite character; 16 people's favourite characters' genders match with their own genders, according to the calculation, it is about 61.54%; the other 4 people's genders don't match with the genders of their favourite characters [8]. However, the percentage of those results are adequate for us to conclude that Disney does consider people's gender identity while designing the characters, and characters may be more attractive to people of the same gender [9].…”
Section: Brand Personalized Customization According To Identitiesmentioning
confidence: 99%
“…Finally, it is concluded that the character's race and gender are unbalanced. Still, with the progress of the times, this phenomenon is shrinking, and most consumers maintain a positive attitude towards this phenomenon [8].…”
Section: Introductionmentioning
confidence: 99%